The Integration of Generative AI in Distance Education on Learning Effectiveness and Academic Integrity: A Systematic Review - Abhik Maiti (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
The integration of Artificial Intelligence (AI) and Big Data has fundamentally transformed distance learning into a highly personalized and data-driven experience. However, this transition poses major obstacles to maintaining academic integrity and rigorous standards in Open and Distance Learning (ODL) environments. The objective of this study is to formulate a strategic roadmap that aligns AI-driven learning optimization with academic rigor. This research employs a qualitative descriptive method through a systematic literature review (SLR) and thematic analysis. Data were synthesized from high-impact academic publications and case studies published between 2023 and 2025, concentrating on strategic implementations in global ODL institutions. The findings identify four critical thematic pillars: faculty training, ethical governance, individualized learning, and assessment redesign. The study reveals that a "human-centric AI" model is vital, where AI serves as an augmentative tool rather than a replacement for human judgment. Institutions must transition toward authentic, process-oriented assessments and robust ethical frameworks to ensure that technological efficiency does not compromise higher-order thinking skills. In practice, this research provides policymakers with a blueprint for creating inclusive and transparent educational ecosystems.